(untitled) (CR. Conservación y Restauración, 2025)
his article centers on the vital role of the restorer-as-investigator in the identification and recovery of historical movable cultural heritage. It examines the restorer’s work within the legal framework concerning the protection and recovery of cultural heritage, detailing his/her specific function, methodology, and relationship to various national and international organizations, while analyzing the specific challenges that emerge in the context of Mexico. The text emphasizes the importance of developing this specialty, the need for both updating extant legislation and optimizing collaborations among various national and international institutions. It offers a reflection on possible ways to make processes of recovery and safeguarding more efficient, focusing on the coordinated effort between them, the centralization and maintenance of a database, as well as the training or personnel and standardization of investigative processes.